1976
DOI: 10.1007/bf01868969
|View full text |Cite
|
Sign up to set email alerts
|

Role of membrane-bound Ca in ghost permeability to Na and K

Abstract: The permeability of red cell ghosts to K is determined by the amount of membrane-bound Mg which, in turn, depends on internal Mg. Contrasting with such effect, an increase in cellular Ca raises K permeability. To test whether this action is due to a competitive displacement of membrane Mg, the free Ca content of human red cell ghosts was altered by means of Ca-EGTA buffers. Net Na and K movements as well as Ca and Mg bindings were assessed after incubation in a Na-medium at 37 degrees C. Raising Ca from 3 X 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…CaZ+-EGTA buffers were calculated as detailed elsewhere [31] and free-Ca 2+ concentrations were checked using commercial electrodes (Radiometer Ca 2+-Selectrodes).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CaZ+-EGTA buffers were calculated as detailed elsewhere [31] and free-Ca 2+ concentrations were checked using commercial electrodes (Radiometer Ca 2+-Selectrodes).…”
Section: Methodsmentioning
confidence: 99%
“…The Ca2+-dependent K + channel of human erythrocytes exhibits a variable Ca 2+ sensitivity, depending on the cellular ATP content and age [11,13,21,31,35,37,39]. Such characteristic may arise from either an all-or-none behavior of K + channels, predominant in an heterogeneous cell population [2,10,11], a variable channel activity among the different cellular subpopulations or both.…”
Section: Introductionmentioning
confidence: 98%
“…This has been reported in the literature from studies that used the fluorescent probe Fura-2 in cells separated on Percoll density gradients, which revealed that in vivo aged RBC (senescent) contained a higher content of free Ca 2+ (almost four times higher) than the younger cells. 35 The consistency of the role of Ca 2+ in the frame of RBC storage is strengthened by the consideration about the role of this ion in modulating the Ca-dependent K channel 36 and the influence on RBC membrane shape. 37,38 Most of the proteins detected through our 2-DE approach, both in the presence and absence of NEM, had already been reported to accumulate in RBC-leaked microand nano-vesicles, for example stomatin, ankyrin, biliverdin reductase, and 14-3-3 zeta/delta (Online Supplementary Table S1 in comparison to the findings of Bosman et al 15 ), just to mention few.…”
Section: Alterations Of Red Blood Cell Membrane Shape and Vesiculatiomentioning
confidence: 99%
“…Such alterations seem to arise from Ca 2+ interactions with various molecular targets. These include both low-affinity associations with membrane phospholipids (Chandra et al, 1987) and high-affinity ones with specific membrane proteins, especially the Ca-dependent K channel (Romero, 1976) as well as with some cytoskeletal proteins (Wallis et al, 1993). It was observed that the presence of the bivalent-cation ionophore A23187 did not induce erythrocyte death in the absence of extracellular Ca 2+ , nor in the presence of both Ca 2+ and the Ca 2+ chelator EDTA, thus characterizing erythrocyte death as an active process requiring Ca 2+ entry into the cells (Bratosin et al, 2001).…”
Section: Intracellular Calcium Contentmentioning
confidence: 99%